Contamination of Legionella pneumophila in metro cooling tower water and its influencing factors in a city - Rong PENG; Bin SHI; Huaiji WANG; Junling LIU; Fang WANG (环境与职业医学)
BackgroundThe detection rates of Legionella pneumophila in metro cooling tower water in various cities are relatively high, while studies investigating the trends of Legionella pneumophila pollution and analyzing its influencing factors are still limited. ObjectiveTo investigate the status of Legionella pneumophila contamination in the water of metro cooling towers in a city, to analyze its influencing factors, and to provide a basis for preventing and controlling Legionella pneumophila contamination in metro cooling tower water. MethodsAfter categorizing the metro lines into three groups (>10 years, >5-10 years, and ≤5 years) according to the operating years of each metro line in a city, we randomly selected one line from each group and the selection resulted a total of 58 cooling towers. We collected water samples from the cooling towers during the early, middle, and late stages of cooling tower operation to detect Legionella pneumophila and water quality related indicators. Information on the environment and hygiene management measures of the cooling towers was obtained through on-site investigation and questionnaire survey. Generalized mixed linear models were used to analyze the influencing factors of Legionella pneumophila contamination in cooling tower water. ResultsThe detection rates of Legionella pneumophila in the early, middle, and late stages of cooling tower operation were 25.9%, 77.6%, and 81.0%, respectively. The detection rates in the middle and late stages of operation were significantly higher than that in the early stage (P<0.001). The results of generalized mixed linear regression showed that the total dissolved solids and conductivity were positively associated with positive Legionella pneumophila. For each unit increase in ln-transformed total dissolved solids and conductivity, their ORs (95%CIs) were 3.73 (1.19, 11.69) and 3.62 (1.07, 12.25), respectively. Nitrates, sulfates, and free residual chlorine were negatively associated with positive Legionella pneumophila. For each unit increase in ln-transformed nitrates and sulfates, their ORs (95%CIs) were 0.52 (0.34, 0.80) and 0.54 (0.36, 0.81), respectively. Compared with the group with 0-0.04 mg·L−1 of free residual chlorine, the ORs (95%CIs) for the groups with 0.05-0.30 mg·L−1 and ≥0.31 mg·L−1 of free residual chlorine were 0.22 (0.07, 0.74) and 0.01 (0.01, 0.19), respectively. Nitrates, sulfates, and free residual chlorine were negatively associated with the concentration of Legionella pneumophila. For each unit increase in ln-transformed nitrates and sulfates, the βs (95%CIs) of Legionella pneumophila concentration were −1.17 (−1.59, −0.74) and −1.11 (−1.63, −0.58), respectively. Compared with the group with 0-0.04 mg·L−1 of free residual chlorine, the β (95%CI) was −5.66 (−9.45, −1.87) for the group with ≥0.31 mg·L−1 of free residual chlorine. ConclusionThe metro cooling tower water in the selected city is seriously contaminated by Legionella pneumophila, and getting further aggravated as the cooling tower annual operation time increases. Total dissolved solids, conductivity, nitrates, sulfates, and free residual chlorine are the major influencing factors for positive Legionella pneumophila, and nitrates, sulfates, and free residual chlorine are the major influencing factors for the concentration of Legionella pneumophila.